2016
DOI: 10.1007/s11368-016-1417-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal distribution of pyrethroids in soil in Mediterranean paddy fields

Abstract: Purpose The demand of rice by the increase in population in many countries has intensified the application of pesticides and the use of poor quality water to irrigate fields. The terrestrial environment is one compartment affected by these situations, where soil is working as a reservoir, retaining organic pollutants. Therefore, it is necessary to develop methods to determine insecticides in soil and monitor susceptible areas to be contaminated, applying adequate techniques to remediate them. Materials and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…A B Generally, multiple SPs are used in rotation instead of repeating a single pyrethroid for a longer time. Therefore, residues of various SPs are found in terrestrial and aquatic environments [50,51]. Different SPs including tetramethrin, permethrin, bifenthrin, allethrin, and chlorempenthrin were separately added to the MSM medium at a final concentration of 50 mg·L −1 .…”
Section: Biodegradation Of D-cyphenothrin In Soilsmentioning
confidence: 99%
“…A B Generally, multiple SPs are used in rotation instead of repeating a single pyrethroid for a longer time. Therefore, residues of various SPs are found in terrestrial and aquatic environments [50,51]. Different SPs including tetramethrin, permethrin, bifenthrin, allethrin, and chlorempenthrin were separately added to the MSM medium at a final concentration of 50 mg·L −1 .…”
Section: Biodegradation Of D-cyphenothrin In Soilsmentioning
confidence: 99%
“…In this study, risk assessment for each pyrethroid was performed by estimating its concentration in the soil that might be washed off through leaching and runoff to surface water by calculating the ECEW max (μg L − 1 ) value using the following Eq. (2) [19]):…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Typically, pesticide monitoring involves laborious analytical methods. Many analytical methods for the extraction and analysis of pyrethroids in the soil based on green analytical chemistry have been proposed [8,15,19,20]. However, the extraction of tropical soil of tea plantation was performed only once [18], and the method was time-consuming, required large volumes (up to 100 mL) of organic solvents, such as acetone and dichloromethane, and used large amount of samples, thus generated massive amounts of laboratory waste during analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This study (Weston et al, 2013)reaffirms the contribution of pyrethroids to sediment toxicity even though sampling was not specifically focused on areas of high pyrethroids use. Pyrethroids were detected at maximum concentrations of 57.0 μgkg −1 before plow and 62.3 μgkg −1 during rice production in the soil in Mediterranean paddy fields, being resmethrin and cyfluthrin the compounds found at higher concentrations (Aznar et al, 2017). Pyrethroids presence was much higher in the sediments of creeks within a residential neighborhood near Roseville (Weston et al, 2005), where cyfluthrin, permethrin, bifenthrin, and cypermethrin were found at maximum concentrations of 169, 335, 437 and 736 μgkg −1 , respectively.…”
Section: Introductionmentioning
confidence: 98%